Recording characteristics of electrical impedance myography needle electrodes. (21st August 2017) - Kwon, H; Rutkove, S B; Sanchez, B
Abstract: Objective : Neurologists and physiatrists need improved tools for the evaluation of skeletal muscle condition. Here we evaluate needle electrical impedance myography (EIM), a new minimally invasive approach to determine muscle status that could ultimately become a bedside tool for the assessment of neuromuscular disorders. Approach : We design and study the recording characteristics of tetrapolar EIM needle electrodes combining theory and finite-element model simulations. We then use these results to build and pilot in vivo an EIM needle electrode in the rat gastrocnemius muscle ( n = 2 ). The dielectric properties of muscle are reported (mean ± standard deviation). Results : The numerical simulations show that the contribution of subcutaneous fat and muscle tissues to needle EIM data is <3% and >97%, respectively, and the sensed volume is 0.70 cm 3 . Apparent resistivity 277 ± 30 Ω cm and relative permittivity ( 1 ± 0.4 ) × 10 5 (dimensionless) measured at 10 kHz are in good agreement with in vivo dielectric properties reported in the literature. Significance : The results presented show the feasibility of measuring muscle impedivity in vivo using a needle electrode from 10 kHz to 1 MHz. The development of needle EIM technology can open up a new field of study in electrodiagnostic medicine, with potential applications to both disease diagnosis and biomarker assessment of therapy.